Organization of microscale objects using a microfabricated optical fiber - Mohanty, S. K. (2008)
We demonstrate the use of a single fiber-optic axicon device for organization of microscopic objects using longitudinal optical binding. Further, by manipulating the shape of the fiber tip, part of the emanating light was made to undergo total internal reflection in the conical tip region, enabling near-field trapping. Near-field trapping resulted in trapping and self-organization of long chains of particles along azimuthal directions (in contrast to the axial direction, observed in the case of large tip cone angle far-field trapping).